2007
DOI: 10.1002/marc.200600572
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Triggered Frontal Polymerization

Abstract: A totally new mode of frontal polymerization (FP) of acrylamide is established which is triggered by the simple addition of a minute, specific volume of water. Experimental conditions under which this mode of polymerization yields linear and water‐soluble polyacrylamide were carefully established, paving the way to synthesize commercially pertinent homo‐ and copolymers. A new redox couple was identified to circumvent the imidization and the ensuing gelation, hitherto associated with FP of acrylamide. Effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…and high initiating capability. 21 FPs initiated by redox couples 2,3,22 and water-triggered FP of acrylamide 23 have been previously reported. Zhou et al recently reported plasmatriggered FP in combination with redox initiator combinations, namely, ammonium persulfate (APS) / N,N,N 0 ,N 0tetramethylethylenediamine (TMEDA).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…and high initiating capability. 21 FPs initiated by redox couples 2,3,22 and water-triggered FP of acrylamide 23 have been previously reported. Zhou et al recently reported plasmatriggered FP in combination with redox initiator combinations, namely, ammonium persulfate (APS) / N,N,N 0 ,N 0tetramethylethylenediamine (TMEDA).…”
mentioning
confidence: 94%
“…Compared with conventional free radical initiators, redox ones possess lower activation energy (40–80 kJ mol −1 ), short induction period, and high initiating capability . FPs initiated by redox couples and water‐triggered FP of acrylamide have been previously reported. Zhou et al recently reported plasma‐triggered FP in combination with redox initiator combinations, namely, ammonium persulfate (APS) / N,N,N′,N′‐tetramethylethylenediamine (TMEDA) …”
Section: Introductionmentioning
confidence: 99%
“…McFarland et al demonstrated free radical FP of 1,6‐hexanediol diacrylate with encapsulated cumene hydroperoxide and cobalt naphthenate 39. Pujari et al recently reported redox FP of acrylamide triggered by traces of water 40. However, redox polymerization has not been thoroughly explored in FP.…”
Section: Introductionmentioning
confidence: 99%
“…Pujari et al triggered FP of acrylamide by the simple addition of a minute, specific volume of water. They investigated the effect of type and concentration of redox couple and volume of water on front velocity, front temperature, and shape of front and yield 17. Chen et al reported the first synthesis of poly( N ‐methylolacrylamide) (PNMA) via free‐radical FP with solid monomers at ambient pressure and claimed that solvent‐free FP could be exploited as a means for preparation of PNMA with the potential advantage of higher throughput than solvent‐based methods 18…”
Section: Introductionmentioning
confidence: 99%